2021
DOI: 10.1007/s00726-021-02953-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo emergence of beige-like fat in chickens as physiological adaptation to cold environments

Abstract: While it has been hypothesized that brown adipocytes responsible for mammalian thermogenesis are absent in birds, the existence of beige fat has yet to be studied directly. The present study tests the hypothesis that beige fat emerges in birds as a mechanism of physiological adaptation to cold environments. Subcutaneous neck adipose tissue from cold-acclimated or triiodothyronine (T3)-treated chickens exhibited increases in the expression of avian uncoupling protein (avUCP, an ortholog of mammalian UCP2 and UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, avian uncoupling protein (avUCP), which shares high homology with human UCP3, has been suggested as an important protein for thermogenesis in avian species such as chicken, hummingbirds, and king penguins [64,65]. In another study on chicken, the avUCP was activated by cold exposure and ADRB stimulation using isoproterenol, contributing to the induction of beige-like adipose tissue [66,67]. These results suggested that the functional role of UCP3 may vary based on the presence of BAT or UCP1 among different animals, and UCP3 may have the ability of browning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, avian uncoupling protein (avUCP), which shares high homology with human UCP3, has been suggested as an important protein for thermogenesis in avian species such as chicken, hummingbirds, and king penguins [64,65]. In another study on chicken, the avUCP was activated by cold exposure and ADRB stimulation using isoproterenol, contributing to the induction of beige-like adipose tissue [66,67]. These results suggested that the functional role of UCP3 may vary based on the presence of BAT or UCP1 among different animals, and UCP3 may have the ability of browning.…”
Section: Discussionmentioning
confidence: 99%
“…In the case that the observed stimulatory effect of diclazuril occurred in treated poultry, this could result in elevated tissue energy expenditure and metabolism by increasing TH-dependent gene expression in the muscle and liver. While it has been thought that BAT-dependent thermogenesis is absent in the chicken, this has been recently questioned by demonstrating the emergence of beige-like fat as a physiological adaptation to cold [ 49 ]. This induction of BAT TH signaling by diclazuril could contribute to non-shivering thermogenesis and energy loss also in the chicken, but further studies are required to directly prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Luijten et al [ 49 ] reported that chronic GC-induced obesity develops independently of UCP1. Recently, Sotome et al [ 50 ] demonstrated that abdominal fat exhibits increased lipolysis probably without increased thermogenesis in white leghorn chickens. Therefore, even though chronic CORT exposure increased browning marker gene expression, white adipose browning could not influence the visceral fat deposition.…”
Section: Discussionmentioning
confidence: 99%